Efektivitas Token Ekonomi Dalam Mengurangi Perilaku Kecanduan Game Online pada Mahasiswa - Fawwaz Zain; Nailassakinah Yahya; Muhammad Jamaluddin (Publikasi Inspirasi Indonesia, 2024)
Addiction to online gaming can be defined as a persistent and obsessive tendency to concentrate on games played through an internet connection while neglecting other activities. Addiction to online gaming is becoming a serious problem for college students, and it has negative effects on their physical, mental, and academic health. The objective of this study was to determine how effective the token economy is in helping college students overcome their online game addiction. It used a single case experimental design with one participant, a student who was addicted to online games. The results of the study indicate that the token economy is effective in reducing behaviors that lead to addiction to online games